Comprehensive geriatric assessment on an acute medical unit: a qualitative study of older people’s and informal carer’s perspectives of the care and treatment received - Darby, Janet; Williamson, Tracey; Logan, Pip; Gladman, John R.F. (SAGE, 2016)
Objective: This qualitative study was imbedded in a randomised controlled trial evaluating the addition of geriatricians to usual care to enable the comprehensive geriatric assessment process with older patients on acute medical units. The qualitative study explored the perspectives of intervention participants on their care and treatment.